Digital Learning Strategies in Improving the Learning Experience of Elementary Students in View of Gender - Khairunnisa (Journal of Contemporary Gender and Child Studies, 2022)
This study aims to describe blended learning in order to improve the experience of elementary school students in terms of gender. This study uses a qualitative description with a phenomenological approach, namely describing or describing the object of study in terms of events as they appear or as they are. The results of the study show that learning can be carried out online using blended learning, so there is a need for full learning focus and attention because students feel happy and challenged when participating in learning activities in class. Student learning experiences are influenced by supporting and inhibiting factors. Students who are physically and mentally healthy as well as good environmental conditions can foster good student interest in learning. Blended learning is very useful for learning during a pandemic like today because it can trigger children's interest in learning and make them more motivated to learn.